2003
DOI: 10.1590/s0103-97332003000400025
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional magnetic properties of cuprates

Abstract: Recently experiments on high critical temperature superconductors have shown that the doping levels and the superconducting gap are usually not uniform properties but strongly dependent on their positions inside a given sample. We show here that the large diamagnetic signal above the critical temperature T c and the unusual temperature dependence of the upper critical field H c2 with the temperature can be explained taking the inomogeneities and a distribution of different local critical temperatures into acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The results obtained for the deformed magnetization are very interesting, because we can compare it with experimental results obtained for superconducting materials (which are perfect diamagnetic materials) as a function of temperature variation [42], in order to strength the understanding of the q-deformation as a factor of impurity. In these references [42] one was found that the minimum of magnetization deepens as temperature or pressure decreases.…”
Section: Fibonacci Oscillators In the Landau Diamagnetismmentioning
confidence: 93%
“…The results obtained for the deformed magnetization are very interesting, because we can compare it with experimental results obtained for superconducting materials (which are perfect diamagnetic materials) as a function of temperature variation [42], in order to strength the understanding of the q-deformation as a factor of impurity. In these references [42] one was found that the minimum of magnetization deepens as temperature or pressure decreases.…”
Section: Fibonacci Oscillators In the Landau Diamagnetismmentioning
confidence: 93%